(untitled) (African Journal of Biomedical Research, 2023)
This study investigated the determinants of sexual behavior among out-of-school adolescents in Ibadan, Nigeria. A cross-sectional study was conducted using a staged sampling technique to select 15-19years 400 out-of-school adolescents. Quantitative data was collected using an interviewer-administered semi-structured questionnaire. Analysis of data was carried out using descriptive and inferential statistics at a level of significance set at 95% confidence level. Mean age of respondents was 17.49 ± 0.06 years and lowest age at sexual debut was 13 years. Majority (67.8%) of respondents were exposed to movies and musicals that promote sexual activities. Less than half (46.3%) of respondents were encouraged by friends to engage in sexual activities while a majority (94.8%) engaged in unsafe sexual practice. There was a statistical significant association between age (p = 0.00), sex (p = 0.04), occupation (p = 0.01) and experience of sexual intercourse. Older respondents (OR= 8.29) and males (R= 0.68) were more likely to have had sexual intercourse. Most out-of-school adolescents were sexually active and majority engaged in unsafe sexual practices. The need for further expansion and strengthening of information and services to adolescents, particularly for the less accessible out-of-school ones, should be encouraged.